A COMPARATIVE ANALYSIS OF GLOBAL COMPETITIVENESS AMONG BRIC NATIONS: IMPLICATIONS FOR CHINA - Mark Kam Loon Loo (International Journal of Organizational Business Excellence, 2018)
Since the acronym BRIC was coined in 2001, the world has touted Brazil, Russia, India and China as the emerging superpowers and engines of growth that would supersede the G7 economies and revive the sagging global economy. By 2010, the Big Four accounted for only 25% of the world’s gross national income despite owning over 25% of land area and over 40% of global population. This paper analyzes the global competitiveness of the BRIC nations over 15 years, in three five-year periods, and finds only China has shown stable growth. What then are the secrets to China’s growth and can China maintain growth? This paper then investigates the performance of China’s pillars of competitiveness and identifies the weak pillars, drawing attention to the issues and making recommendations for sustainable growth.